STRATEGI PEMASARAN PRODUK PEMBIAYAAN DENGAN ANALISIS SWOT - Asnawi, Habib Shulton; Suhendri, Aan; Ambariyani, Ambariyani (KHOZANA: Journal of Islamic Economic and Banking, 2020)
Marketing strategy is the spearhead for a financial institution to introduce and market the advantages of its products. Marketing strategy can be done by using a marketing mix strategy which is a tool for marketers consisting of various elements of marketing programs such as product, price, place and promotion. In this study, the authors formulated the problem of how the marketing strategy for financing products at BMT Assyafi'iyah Berkah Nasional Pekalongan East Lampung branch and how the marketing strategy through SWOT analysis on mudharabah financing products at BMT Assyafi'iyah Berkah Nasional Pekalongan branch, East Lampung. To obtain the data in this study, the researchers used several research methods, namely this type of research using field research. The data source of this research uses primary, secondary and tertiary data sources. Meanwhile, the data collection method uses observation, interviews and documentation and uses the Snawoball sampling method and questionnaire. The result of this research is the marketing strategy applied to BMT Assyafi'iyah Pekalongan East Lampung Branch, namely using product marketing strategies, price, place, and promotion. The result of the SWOT analysis above shows that BMT Assyafi'iyah Pekalongan East Lampung Branch shows at the quadrant II level by means of a diversification strategy.